2004
DOI: 10.1002/maco.200303724
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microstructural changes on corrosion behaviour of thermally aged Ti‐6Al‐7Nb alloy

Abstract: Solution treatment and ageing (STA) is an effective strengthening method for a þ b titanium alloys. This paper reports the effect of solution treatment and aging on the corrosion behaviour of Ti6Al-7Nb alloy in a simulated body fluid (Ringer's solution). Ti6Al-7Nb alloy is hot rolled in the a þ b field and subjected to solution treatment above and below its beta transus temperature (1283 K). The solution treated specimens are water quenched (WQ), air-cooled (AC), and furnace cooled (FC) at three different rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…It was observed that the corrosion resistance of titanium alloys with Nb and Fe is marginally better than that of the Ti6Al4V alloy under physiological conditions (pH ¼ 8). This was explained by the lower solubility of the Nb ion in comparison with Al and V in the Ti6Al4V [21].…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the corrosion resistance of titanium alloys with Nb and Fe is marginally better than that of the Ti6Al4V alloy under physiological conditions (pH ¼ 8). This was explained by the lower solubility of the Nb ion in comparison with Al and V in the Ti6Al4V [21].…”
Section: Resultsmentioning
confidence: 99%
“…Some authors (12) report that Ta addition decreases corrosion in titanium alloys thanks to formation of Ta 2 O 5 on the upper surface that strongly reduces exchange of ions between material and surrounding tissue. There is a signifi cant reduction of the exchange rate when compared to those titanium alloys forming only TiO 2 (13). Therefore, titanium alloys having Ta are considered promising dental materials with minimized corrosion behavior (14).…”
Section: Introductionmentioning
confidence: 99%
“…The corrosion resistance of the titanium bioalloys varies with their composition, structural statement as a result of thermo-mechanical processing and with the content of the biofluid [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Of special interest for biomedical applications are the alloys: Ti-6Al-7Nb [23,24], Ti-13Nb-13Zr [8,17], Ti-15Mo-5Zr-3Al (developed by Kobe Steel Ltd., Japan) [33], Ti-12Mo-6Zr-2Fe [34], Ti-30Nb, Ti-30Ta [35], etc.…”
Section: Introductionmentioning
confidence: 99%